Pendidikan Karakter Dalam Membangun Moderasi Beragama Generasi Milenial di MA El-Bayan Majenang - Siti Uswatun Hasanah; Rena Sulistyaningrum (Departement of Mathematics Education, 2023)
This study aims to explore the implementation of character education in building religious moderation in MA El-Bayan Majenang. By conducting this research, it is hoped that it can provide an overview of the character education practices carried out at MA El-Bayan Majenang. The author also hopes that this research can provide useful information about the implementation of character education in building religious moderation in the millennial generation at MA El-Bayan Majenang. The research method used is descriptive method with a qualitative approach. Data were collected through observation, interviews and documentation studies. Research participants included teachers, students, and school staff involved in implementing character education at MA El-Bayan Majenang. The results of the research show that character education is an important effort in educating children to be able to make wise decisions and apply them in everyday life. Implementation of character education at MA El-Bayan Majenang through religious activities has succeeded in growing and increasing students' sense of religiosity. In this context, the millennial generation at MA El-Bayan Majenang shows a positive level of religious moderation. Based on the results of this study, it can be concluded that character education is an important component in building religious moderation in the millennial generation at MA El-Bayan Majenang. The practice of character education through religious activities can make a positive contribution in forming strong and moderate religious attitudes in students. These findings provide a better understanding of the importance of character education in the context of building religious moderation in the millennial generation.